U.S. Food and Drug Administration Approves Paclitaxel Protein-Bound Particles (Abraxane®) in Combination with Gemcitabine as First-Line Treatment of Patients with Metastatic Pancreatic Cancer - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
No abstract available